Analysis of physics e-modules based on guided inquiry integrated with Quran knowledge - Dona, Prisma; Syafriani, S (Journal of physics. Conference series, 2020)
The era of Industrial Revolution 4.0 is an era where human life is always related to technology, including in the field of education. Every teacher is required to be adept at using information technology in the implementation of learning. One example of the use of technology by teachers is the use of electronic teaching materials. In addition to the use of technology, teachers also associate learning material with the Qur'an. So that students can understand learning not only from physical theory, but also from Islamic studies. Therefore, it is necessary to analyze the teaching materials used by the teacher in conducting learning in school. This research is a descriptive research. The method used is in the form of interviews and questionnaires for physics subject teachers and students. The results of the study show that the teaching materials used are still in the form of printed textbooks that are sold on the market and printed modules prepared by the teacher. The modules compiled by the teacher have not yet used the learning model so that they have not been able to guide students to be able to learn independently from the module. The module also has not linked physics, material with the insights of the Qur'an. So it is necessary to develop a guided inquiry-based physics e-module integrated in the Qur'an